Peningkatan Skala Percobaan (Scale Up Experiment) Pengolahan Limbah Cair Sawit secara Aerobik Menggunakan Teknologi Simbiosis Mutualisme Mikroalga Chlorella sp. dan Agrobost - Yuliandri, Fajar; Restuhadi, Fajar; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This research was aimed to get the best various additions of Agrobost which symbiotic microalgae Chlorellasp. in accelerating to reduce of pollutants level in palm oil mill effluent using the scale up experimenttechnology. This research used Completely Randomized Design with 5 treatments and 3 repetition. This research used microalgae(with abundance ± 6,985,000 cfu/ml) and palm oil mill effluent with 5 treatments of Agrobost (0% v/v, 4% v/v, 8% v/v, 12% v/v and 16% v/v). The data were obtained from statistical analytic using ANOVA and DNMRT in 5% level. The results showed that the concentration of Agrobost had significant affects for nitrate and phosphate. The selected treatment was 16% v/v addition Agrobost with the highest reduction level had nitrate of 3.40 mg.L-1 and phosphate of 8.18 mg.L-1. Keywords:palm oil mill effluent, Agrobost, microalgae Chlorella sp., scale up